The cross-cultural identity in the notions of Ubuntu of Augustine Shutte and Kwame Gyekye - Anofuechi, Benson Onyekachukwu (Stellenbosch Theological Journal, 2024)
This research seeks to make a unique contribution to moving identities by investigating ubuntu as a formation process of identity across different cultures. In African society, ubuntu as a notion of African humanism has been and is still subject to criticism. In African literature, anthropology, ethics, philosophy, and theology, ubuntu does play a role and scholars in Africa and beyond find the notion a contested one. The concept and approach to identity formation on the African continent has been written about widely. The article unpacked the notions of ubuntu of (Augustine Shutte) and (Kwame Gyekye). The views of these scholars will be juxtaposed to engage critically the possible comparisons for identity across cultures. The article addressed the commonalities and contestation of ubuntu as basis of identity formation. The article further explores the two African thinkers’ understanding and assessed the relevance of ubuntu in contemporary Africa with an unprecedented number of migrants from various parts of Africa.